Factores de riesgo y malnutrición en niños de área urbana. Riobamba, 2017- 2020 - Estrella Viscarra, Nathalia Lizbeth (2020)
Infant malnutrition is a global health issue and of growing importance in our country. National statistics show that 25% children of the ages 0 – 5 suffer from chronic malnutrition. Chimborazo is one of the provinces that has been one of the most affected with a 48% which cannot be cured or corrected in later stages of life because of increasing malnutrition rates which raise up to 30 to 35%. Objective: Determine Urban Risk Factors and Malnutrition in Children. Methods and Material: Descriptive, experimental, transversal, and retrospective studies were done using deductive and analytical methods based on clinical history and surveys during the medical consult. Results: The study was done in urban areas and was conformed of 428 children of which 60,05% of the children girls. It was determined that 40,4% of those children were being affected by malnourishment, 15.19% malnutrition, and 7.71% of being overweight 36,68%. being the number of normal weight children. The main risk factors are the inadequate food intake, the marital status of the mother since 35.5% are heads of families, and finally the characteristics during pregnancy; 32.94% of the mothers presented malnutrition, 18.46% were overweight mothers, which influences an important factor within the nutritional status.